PERDARAHAN INTRASEREBRAL SEBAGAI KOMPLIKASI NEUROLOGI EMBOLI SEPTIK PADA ENDOKARDITIS INFEKTIF: SEBUAH LAPORAN KASUS - Mohammad Kurniawan; Salim Harris; Al Rasyid; Taufik Mesiano; Rakhmad Hidayat; Yesi Astri (NEURONA, 2019)
INTRACEREBRAL HEMORRHAGE AS A NEUROLOGICAL COMPLICATION OF SEPTIC EMBOLISM IN INFECTIVE ENDOCARDITIS: A CASE REPORTABSTRACTInfective endocarditis (IE) is a life-threatening disease. The incidence of IE in developing countries is reported at 1.7-6.2 per 100,000 individuals per year. IE is also known as a potential condition for embolization, especially septic embolism to the brain. Septic embolism results in various neurological complications and manifestations due to vascular occlusion, aneurysm formation and rupture of the aneurysm. We report a case of 34-year-old male with definitive IE based on Duke criteria who experienced neurological complications of intracerebral bleeding. Patient was given pharmacological treatment according to the guidelines of the American Heart Association (AHA)with improvement in clinical symptoms.Keywords: Infective endocarditis, intracerebral hemorrhage, septic embolismABSTRAKEndokarditis infektif (EI) merupakan penyakit yang mengancam nyawa, walaupun angka kejadiannya kecil, yaitu 1,7-6,2 per 100.000 individu per tahun di negara berkembang. EI juga sangat potensial menyebabkan embolisasi, khususnya emboli septik ke otak. Emboli ini mengakibatkan manifestasi gangguan neurologis yang disebabkan karena oklusi pembuluh pembentukan dan ruptur aneurisma. Dilaporkan kasus seorang laki-laki 34 tahun dengan EI definitif berdasarkan kriteria Duke yang mengalami komplikasi neurologis perdarahan intraserebral. Pasien ditatalaksana sesuai panduan American Heart Association (AHA) dengan perbaikan gejala klinis.Kata kunci: Endokarditis infektif, emboli septik, perdarahan intrakranial